(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Are presented the results of three-year studies on the complex impact of various combinations of seed sowing rates with row spacing on the elements of plant productivity and grain yield of winter wheat of the intensive variety Bogdana in the conditions of the Eastern Forest Steppe of Ukraine. Formulation of the problem. Despite the seemingly sufficient study of the influence of seed sowing rate and row width on the formation of plant productivity and grain yield of winter wheat, it is still relevant. High yield of this crop can be obtained with the optimal density and nature of the distribution of plants over the area, taking into account the morphological and biological specificity of the varieties. Based on this, the purpose of the research was to determine the complex impact of various combinations of row width and seed sowing rate on the elements of plant productivity and grain yield of winter wheat in the conditions of the eastern forest-steppe of Ukraine. Research methods. The research was carried out in 2023–2024 on the basis of the educational and scientific production center «Dokuchaevske» of the State Biotechnological University. The two-factor experiment was carried out using the method of split plots in three repetition in one tier. The plots of the first order (factor A) were three variants of the width of the row: 1 – 15 cm (control); 2 – 30 cm and 3 – 15+30 cm (the distance between the rows in the tape is 15 cm, and the distance between the tapes is 30 cm). The plots of the second order (factor B) were four variants of the seed sowing rate: 400; 450; 500 and 550 pcs./m2. The area of the sown and accounting plot of the second order was 40.0 and 30.0 m2, respectively. Weather condition during the growing season of winter wheat crops in the research years differed significantly both in terms of temperature and rainfall. In 2022–2023, they were favorable, and in 2023–2024, on the contrary, they were unfavorable. At the time, they differed most precisely in the conditions of the spring and summer periods. Thus, in the period from April to July inclusive in 2023, 255 mm of precipitation fell, while in the 2024 – only 62 mm. Research results. In the conducted experiment, the high efficiency of the studied factors on the formation of plant productivity indicators was established. The largest number of seeds per plant was in the variants of the combination of the lowest seed sowing rate of 400 pcs./m2 with row spacing of 15+30 cm – 44.7 pcs. in 2023 and 33.0 pcs. – in 2024. The influence of the studied factors on the change in the mass of 1000 grain was practically absent. At the same time, a tendency towards its increase was noted under the condition of decreasing competition between plants, that is, decreasing the rate of sowing seeds and narrowing the rows. In general, this is natural, because the mass of 1000 is a deterministic varietal characteristic, which does not change much under the influence of various options for growing technology. The influence of the studied factors on the mass of grain from a plant was higher than on its grain size, and this is logical, because a decrease in the density of plants led to the formation of a larger number of grain on the plant, and to an increase in the mass of 1000 grains. In general, according to the experiment, the largest mass of grain from a plant was on the variants of the combination of the seed sowing rate of 400 pcs./m2 with row spacing according to the scheme of 15+30 cm – 1.98 g in 2023 and 1.35 g – in 2024. Following plant productivity indicators, higher sowing rates showed an advantage in the number of plants per unit area. Quite logically, the largest number of plants for all variants of row spacing was at the rate of seed sowing of 550 pcs./m2. Therefore, the regularity of the influence of the studied factors on the elements of plant productivity and their density before harvesting differed. With a decrease in the rate of sowing seeds, productivity indicators increased, but the number of plant per unit area decreased. Conclusions. For all studied seed sowing rates, the higher grain yield of winter wheat was in variants with row spacing according to the scheme of 15+30 cm. At the same time, the highest yield for these rows was formed at the seed sowing rate of 500 pcs./m2 – 6.09 t/ha in 2023 and 3.80 t/ha – in 2024. A further increase in the rate of seed sowing did not ensure an increase in grain yield. It is important to emphasize that such results were obtained in years that differed significantly in terms of weather conditions, which gives reason to recommend this combination of seed sowing rate and row spacing for sowing winter wheat in both favorable and arid growing regions.